Lessons Learned After 760 Neurointerventions via the Upper Extremity Vasculature: Pearls and Pitfalls. Issue 6 (16th April 2021) - Sweid, Ahmad; Weinberg, Joshua H; Khanna, Omaditya; Das, Somnath; Kim, Julie; Curtis, Darcy; Hammoud, Batoul; El Naamani, Kareem; Abbas, Rawad; Majmundar, Shyam; Sajja, Kalyan C; Chalouhi, Nohra; et al.
Abstract: BACKGROUND: The radial approach has been gaining more widespread use by neurointerventionalists fueled by data from the cardiology literature showing better safety and overall reduced morbidity. OBJECTIVE: To present our institution's experience with the radial approach for neuroendovascular interventions in 614 consecutive patients who underwent a cumulative of 760 procedures. METHODS: A retrospective analysis was performed and identified neuroendovascular procedures performed via the upper extremity vasculature access site. RESULTS: Amongst 760 procedures, 34.2% (260) were therapeutic, and 65.7% (500) were nontherapeutic angiograms. Access sites were 71.5% (544) via a conventional radial artery, 27.8% (211) via a distal radial artery, 0.5% (4) via an ulnar artery, and 0.1% (1) via the brachial artery. Most of the procedures (96.9%) were performed via the right-sided (737), 2.9% (22) via the left-sided, and 0.1% (1) via a bilateral approach. Major access site complications occurred at a rate of 0.9% (7). The rate of transfemoral conversion was 4.7% (36). There was a statistically higher incidence of transfemoral conversion when repeat procedures were performed using the same access site. Also, there was no significant difference between nontherapeutic procedures performed using the right and left radial access, and conventional versus distal radial access. Procedural metrics improved after completion of 14 procedures, indicating a learning curve that should be surpassed by operators to reach optimal outcomes. CONCLUSION: Radial artery catheterization is a safe and effective means of carrying out a wide range of neuroendovascular procedures associated with excellent clinical outcomes and an overall low rate of periprocedural complications.